Understanding Kashmir Conflict: Looking for its Resolution - Wani, Hilal Ahmad; Suwirta, Andi (SUSURGALUR, 2013)
ABSTRACT: The most dangerous place in the world today is the Indian sub-continent and the line of control in Kashmir. Kashmir conflict is the outcome of a process of neglect, discrimination, suppression of Kashmir identity, and the pre-eminence of power centric approach held by the successive regimes of India and Pakistan. This paper is new attempt to include ideas of different academic scholars towards a lasting solution to the Kashmir imbroglio. The problem of Kashmir conflict is mostly a constitutional problem. Therefore, this paper includes particularly the dimension of autonomy debate for the resolution of conflict. The autonomy of the Kashmiri people was always curtailed either through the massive violations of human rights or by doing several amendments in the constitution of state. The so called democratic system of India can only be successful in Kashmir when the rights of the people will be safeguarded. This is the main dimension towards a keen interest is needed. India has to understand what are the causes of alienation in Kashmir. Lasting solution to Kashmir conflict different viewpoints of various scholars has been included in this paper.KEY WORD: Kashmir conflict, violations of human rights, India and Pakistan, autonomy, fraud election, and scholars views for resolution.RESUME: Makalah ini berjudul âMemahami Konflik Kashmir: Mencari Penyelesaiannyaâ. Tempat paling berbahaya di dunia saat ini adalah sub-benua India dan garis kontrol di Kashmir. Konflik Kashmir adalah hasil dari suatu proses penelantaran, diskriminasi, penindasan terhadap identitas Kashmir, serta keunggulan dari pendekatan kekuasaan sentris yang dipegang oleh rezim silih berganti dari India dan Pakistan. Tulisan ini adalah upaya baru untuk memasukkan ide-ide akademik para sarjana yang beragam terhadap penyelesaian akhir untuk keruwetan Kashmir. Masalah konflik Kashmir sebagian besar adalah masalah konstitusional. Oleh karena itu, makalah ini khususnya meliputi dimensi debat otonomi untuk penyelesaian konflik. Otonomi rakyat Kashmir selalu dibatasi, baik melalui pelanggaran besar-besaran hak asasi manusia atau dengan melakukan beberapa perubahan dalam konstitusi negara. Apa yang disebut dengan sistem demokrasi di India hanya dapat berhasil di Kashmir ketika hak-hak rakyat akan terlindungi. Ini adalah dimensi utama menuju kepentingan yang diperlukan. India harus memahami apa-apa yang menjadi penyebab keterasingan di Kashmir. Penyelesaian akhir ke atas konflik Kashmir dari berbagai sudut pandang para sarjana yang beragam telah dimasukkan dalam makalah ini.KATA KUNCI: Konflik Kashmir, pelanggaran hak asasi manusia, India dan Pakistan, otonomi, pemilihan umum penipuan, dan pandangan para sarjana untuk resolusi.Â Â About the Authors: Dr. Hilal Ahmad Wani is a Post Doctoral Fellow at the Centre for Peace and Strategic Studies UoI (University of Ilorin) in Nigeria; and Andi Suwirta, M.Hum. is a Senior Lecturer at the Faculty of Social Studies Education UPI (Indonesia University of Education) in Bandung. The authorsâ e-mails are: wanihilal@gmail.com and andisuwirta@yahoo.comHow to cite this article? Wani, Hilal Ahmad & Andi Suwirta. (2013). âUnderstanding Kashmir Conflict: Looking for its Resolutionâ in SUSURGALUR: Jurnal Kajian Sejarah & Pendidikan Sejarah, Vol.1(2), September, pp.179-192. Bandung, Indonesia: Minda Masagi Press and UBD Bandar Seri Begawan, Brunei Darussalam, ISSN 2302-5808. Chronicle of the article: Accepted (June 1, 2013); Revised (August 17, 2013); and Published (September 30, 2013).